NEW SPECIES OF CHILEAN COLLETIDAE (HYMEMOPTERA: COLLETIDAE) (Acta Entomológica Chilena, 2022)
This paper presents the description of four new species of Colletes with metallic blue-green metasoma. The eight species of chilean Colletes with this characteristic are keyed. The new species are: chusmiza, guanta, quelu y vicugnensis.